Emerging Materials and Designs for Low‐ and Multi‐Band Electromagnetic Wave Absorbers: The Search for Dielectric and Magnetic Synergy?. (13th April 2022) - Cheng, Junye; Zhang, Huibin; Ning, Mingqiang; Raza, Hassan; Zhang, Deqing; Zheng, Guangping; Zheng, Qingbin; Che, Renchao
Abstract: Vigorous development of 5G communication technologies can boost mobile networks yet bring in electromagnetic interferences and safety concerns in utilizing electronic devices. Particularly, 5G network can not only involve a low‐frequency band of n 78 (3.3–3.8 GHz) but also cover multi‐frequency bands of n 77 (3.3–4.2 GHz) and n 79 (4.4–5.0 GHz), displaying multiple electromagnetic radiations. Countless efforts have been devoted to investigating electromagnetic wave (EMW) absorbers with low‐ and multi‐band absorption properties. However, in terms of emerging materials and designs, few reports propose the mechanisms related to those properties. This perspective briefly reviews the impressive achievements of low‐ and multi‐frequency EMW absorbers and analyzes the design strategies that may enable low‐ and multi‐frequency absorption. Furthermore, the cutting‐edge mechanisms of corresponding electromagnetic responses, such as Snoek limit, quarter wavelength, and dielectric‐magnetic synergy effects are elaborated. Thus, this perspective can shed light on the new trends and ongoing challenges for EMW absorbers and further promote their practical application. Abstract : In this perspective, significant advances, potential electromagnetic wave attenuation mechanisms, and the corresponding design strategies to achieve low‐ and multi‐frequency electromagnetic absorbers are rationally summarized. Meanwhile, the perspectives for new trends and ongoing challenges in this field are also provided for their future research directions.